The Referendum in Switzerland, by Simon Deploige,... with a letter on the referendum in Belgium, by M. J. Van den Heuvel,... Translated into English by C. P. Trevelyan,... Edited with notes, introduction and appendices, by Lilian Tomn, - Deploige, Simon
Studies in economics and political science. 4